Adaptive backstepping sliding mode control of a grid interactive PV-VSC system with LCL filter. (June 2016) - Dhar, S.; Dash, P.K.
Abstract: This study deals with a new nonlinear backstepping sliding mode control for Photovoltaic (PV) based grid interactive voltage source converter (VSC) system. The VSC dynamic design is incorporated with a low pass LCL filter prior to utility grid connectivity, which is expressed in terms of active ( P 1 ) and reactive ( Q 1 ) power. Low pass LCL filter is introduced as passive ac element and hence a reduced harmonic profile is obtained in terms of total harmonic distortion (THD). The aim of the work is to arbitrate between dynamic performance and filtering effect of the proposed PV-VSC system to provide better reliability with superior power quality. To design a robust control theory with grid uncertainty eradication capability, a new finite time backstepping sliding mode control (FTBFSMC) is proposed in this paper. The control method is implemented in terms of reactive power at PCC ( Q 1 ) and dc side converter voltage ( V p v ), where the converter dynamics are being calculated directly from instantaneous values of converter current ( I i, a b c ) and bus voltage ( V 1, a b c ) to avoid PLL angle calculation at the beginning. A new small signal stability phenomenon is depicted by multivariable dynamic model of the proposed PV based grid converter system, where PV penetration as well as nonlinear control parameter optimization practices is considered. The performance of the proposed control is verified through various case studies in MATLAB/ script environment, which are being extended to MATLAB/Simulink model as well as PSCAD/EMTDC platform for validation.